Anticoagulant-induced hemopericardium with tamponade: A case report and review of the literature. Issue 2 (2013) - Ertaş, Faruk; Polat, Nihat; Yıldız, Abdulkadir; Oylumlu, Mustafa; Ülgen, Mehmet Sıddık
No abstract available